(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research aims to clarify the impact of adopting the IFRS16 financial reporting standard on lease contracts in insurance companies on audit procedures. The change in the classification of lease contracts in the case of adopting the IFRS16 financial reporting standard necessarily requires audit procedures that are compatible with this change. A proposed audit program was prepared, guided by international auditing standards, based on the study of the client’s environment and analysis of external and internal risks in the light of financial and non-financial indicators. The researchers reached a set of conclusions, most notably that the adoption of IFRS16 in insurance companies plays a major role in enhancing the quality of financial reporting and disclosure, which naturally indicates the quality of accounting information. The changes in the classification of lease contracts when adopting the IFRS16 financial reporting standard from an expense to an asset necessitated the introduction of new procedures to keep pace with this fundamental change, which audits lease contracts in terms of calculation, presentation, and disclosure on both sides of the contract (lessor and lessee). Accordingly, the researchers proposed several recommendations, the most important of which is the need for the auditor to rely on an audit program that clarifies all procedures that contribute to reducing the risks of the lease contract auditing process, based on international auditing standards, to reach a reading of the financial statements that is more clear and transparent.